2022
DOI: 10.1136/bmjopen-2021-058132
|View full text |Cite
|
Sign up to set email alerts
|

Sintilimab combined with bevacizumab in relapsed/persistent ovarian clear cell carcinoma (INOVA): an investigator-initiated, multicentre clinical trial—a study protocol of clinical trial

Abstract: BackgroundOvarian clear cell carcinoma (OCCC) has an abysmal prognosis with a median overall survival (OS) of 25.3 months because of a low response to chemotherapy. The 5-year disease-specific survival rate after recurrence is 13.2%, with more than two-thirds of the patients dying within a year. Therefore, it is urgent to explore new therapeutic options for OCCC. Based on the characteristic immune-suppressive tumour microenvironment derived from the gene expression profile of OCCC, the combination of immunoant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Interestingly, in some trials, patients with OCCC appeared to benefit more from ICI therapy. Consequently, dedicated trials have tested ICI in this population and reported encouraging responses with 11-25% ORR and up to 38.5% when associated with bevacizumab ( 249 251 ). Disappointingly, the only randomized trial comparing single-agent chemotherapy to durvalumab (PD-1 inhibitor) in OCCC patients, did not show improved outcomes in the ICI arm, highlighting the need for better biomarkers ( 249 ).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Interestingly, in some trials, patients with OCCC appeared to benefit more from ICI therapy. Consequently, dedicated trials have tested ICI in this population and reported encouraging responses with 11-25% ORR and up to 38.5% when associated with bevacizumab ( 249 251 ). Disappointingly, the only randomized trial comparing single-agent chemotherapy to durvalumab (PD-1 inhibitor) in OCCC patients, did not show improved outcomes in the ICI arm, highlighting the need for better biomarkers ( 249 ).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%